Costing of service: A case study of commercial banks in Malaysia - Abdullah, Zarifah; Ali, Amin; Ishak, Rokiah (Universiti Utara Malaysia, 2003)
Cost information is undeniably a very important piece of information to enable efficient and effective decision-makings on the part of managers. Many studies have been conducted on costing approaches adopted by profit-making organizations, especially those companies in the manufacturing sector. Few studies have been conducted on costing approaches adopted by service organizations such as the banking institutions. However, no such study has yet been conducted on commercial banks in Malaysia.Hence,the purpose of this study to identify the costing methods being used by the commercial banks in Malaysia, in costing their services. Chief Executive Officers from twenty six (26) commercial banks have been approached to get permission for us to conduct interviews with the financial controller of the various banks.From the three (3) participating banks, it was found that none of the banks has actually conducted a proper and systematic costing of their products and services. The banks do not actually know the cost of providing each product and service because none of them carried out a per unit costing on their products and services. Their main concern is, as long as the benefits to be derived from offering such products and services still outweigh the existing costs and the additional costs to be incurred, in totality, the banks will continue to provide such services and products.